Off-centered practices of image and writing in dictatorship: No-vásquez, Bernardo González and Loreto Pérez, Tatiana Álamos and Tristán Altagracia (ALPHA. Journal of Arts, Literature and Philosophy, 2025)
The article approaches to migrations and folds between poetry and visuality in three works of the canonical frameworks of chilean poetry. This works (No Vásquez’s L&vertad, Barrio Cívico. Epigramas, from Bernardo González and Loreto Pérez; Santiago Espiritual en el Nuevo Extremo de la Vida, of Tatiana Álamos y Tristán Altagracia) suggest a poetical expansion as a response to the authoritarian regime by and artistic displacement and artesanal job with precarious materials wich integrate text and images. From the extension of genders and disciplines, focusing on the relationships between graphic and poetic resistance, this three works exceeds the literary and visual frameworks, following the route of expanded poetry in the Pinochet’s dictatorship.
Keywords: Chilean poetry, visual arts, dictatorship, artesanal job